2006
DOI: 10.17221/4511-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Ecological valence of expanding European ash (Fraxinus excelsior L.) in the Bohemian Karst (Czech Republic)

Abstract: ABSTRACT:In 2002 a study focused on the evaluation of height and density of expanding natural regeneration of Fraxinus excelsior L. (FE) was carried out on Velká hora Hill, a locality in the Bohemian Karst (Český kras). The examined area is located in Karlštejn National Nature Reserve and takes up around 31 ha. The parent rock is limestone. The expansion depends on soil and exposition conditions and relates to the water balance gradient. FE reached the highest densities (up to 6,000 individuals/400 m 2 ) on Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…This trend is obviously the direct reason for the expansion of F. excelsior, as reported from several other places (Hofmeister et al, 2004;Střeštík & Šamonil, 2006;von Oheimb & Brunet, 2007). The expansion of nutrient-demanding species is consistent with the observed increase in mean Ellenberg indicator value for nutrients.…”
Section: Species and Vegetation Changesupporting
confidence: 89%
“…This trend is obviously the direct reason for the expansion of F. excelsior, as reported from several other places (Hofmeister et al, 2004;Střeštík & Šamonil, 2006;von Oheimb & Brunet, 2007). The expansion of nutrient-demanding species is consistent with the observed increase in mean Ellenberg indicator value for nutrients.…”
Section: Species and Vegetation Changesupporting
confidence: 89%
“…Ash productivity is strongly influenced by soil composition, climate factors and silviculture. Species thrives on rather deep, humid, fertile, heavy and partially decalcified soils (Střeštík & Šamonil, 2006;Dobrowolska et al, 2011). In term of climatic factors, correlation was generally the strongest between ash increment and temperature compared to precipitation on study plots, especially in the winter and second half of growing season.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, ash establishment may be limited on optimum sites for beech. Thus, a correlation between canopy openness and mean density of ash seedlings was found by Modrý, Hubený & Rejšek (), and Střeštil and Šammonil () found that ash could not establish itself under beech on south‐facing slopes on limestone in the continental climate of the Czech Republic.…”
Section: Response To Environmentmentioning
confidence: 82%
“…It was found in southern Sweden that ash seedling densities were higher in deciduous woodlands than in stands including conifers (Götmark et al . ), and Střeštil & Šammonil () found faster growth of ash seedlings in the Czech Republic in Fageto–Quercetum illimerosum than in the Carpineto–Aceretum saxatile community. On good sites, Kerr () found little evidence of intraspecific competition and in monoculture plantations, ash increased in height, diameter and stem volume with a decrease in spacing from 4.86 to 0.77 m between trees although Kuehne et al .…”
Section: Response To Environmentmentioning
confidence: 94%